PsAA9A, a C1-specific AA9 lytic polysaccharide monooxygenase from the white-rot basidiomycete Pycnoporus sanguineus - Garrido, Mercedes Maria (2020)
Woody biomass represents an important source of carbon on earth, and its global recycling is highly dependent on Agaricomycetes fungi. White-rot Basidiomycetes are a very important group in this regard, as they possess a large and diverse enzymatic repertoire for biomass decomposition. Among these enzymes, the recently discovered lytic polysaccharide monooxygenases (LPMOs) have revolutionized biomass processing with their novel oxidative mechanism of action. The strikingly high representation of LPMOs in fungal genomes raises the question of their functional versatility. In this work, we studied an AA9 LPMO from the white-rot basidiomycete Pycnoporus sanguineus, PsAA9A. Successfully produced as a recombinant secreted protein in Pichia pastoris, PsAA9A was found to be a C1-specific LPMO active on cellulosic substrates, generating native and oxidized cello-oligosaccharides in the presence of an external electron donor. PsAA9A boosted cellulolytic activity of glysoside hydrolases from families GH1, GH5, and GH6.This study serves as a starting point towards understanding the functional versatility and biotechnological potential of this enzymatic family, highly represented in wood decay fungi, in Pycnoporus genus.